2021
DOI: 10.1042/ebc20200178
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella oneidensis MR-1 as a bacterial platform for electro-biotechnology

Abstract: The genus Shewanella comprises over 70 species of heterotrophic bacteria with versatile respiratory capacities. Some of these bacteria are known to be pathogens of fishes and animals, while many are non-pathogens considered to play important roles in the global carbon cycle. A representative strain is Shewanella oneidensis MR-1 that has been intensively studied for its ability to respire diverse electron acceptors, such as oxygen, nitrate, sulfur compounds, metals, and organics. In addition, studies have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…EET is a sophisticated network that involves the coordination of multiple intermediates and complex interactions ( Lubner et al, 2017 ; Ikeda et al, 2021 ). Thus, many in-depth targets might also lead to unexpected improvement for the desired phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…EET is a sophisticated network that involves the coordination of multiple intermediates and complex interactions ( Lubner et al, 2017 ; Ikeda et al, 2021 ). Thus, many in-depth targets might also lead to unexpected improvement for the desired phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the above-mentioned differences, these EET pathways are conduits of electrons, facilitating electrons transfer in both directions (either from the inside to outside or from the outside to inside). For instance, the EET pathway of Shewanella oneidensis has a shallow gradient of redox potential (it gradually increases from the inside to outside), resulting in relatively high anodic current to high-potential electrodes compared to cathodic current from low-potential electrodes ( Ikeda et al, 2021 ). These observations suggest that EET pathways can be used for controlling intracellular redox states (e.g., redox balances of NAD+/NADH) using extracellular electrodes whose potentials are arbitrarily set in BESs.…”
Section: Concepts Of Electro-fermentationmentioning
confidence: 99%
“…It is however unfortunate that the wild-type strain of S. oneidensis is incapable of glucose utilization ( Hirose et al, 2019a ), while a study has shown that introduction of two genes encoding sugar permease and hexose kinase in Escherichia coli facilitates this bacterium to grow on glucose ( Nakagawa et al, 2015 ). In addition, since it has been known that expression of catabolic enzymes and electron-transport proteins in S. oneidensis is complexly regulated at the transcription level ( Hirose et al, 2018 ), further studies on its regulatory mechanisms would be necessary for EF to efficiently utilize designed catabolic pathways ( Ikeda et al, 2021 ). Another EAB that is genetically accessible is Geobacter sulfurreducens ; the use of this bacterium in BESs is attractive in terms of its high electrochemical activity ( Ueki, 2021 ), while genetic manipulation of this bacterium would be more difficult than S. oneidensis owing to its inability to grow aerobically.…”
Section: Concepts Of Electro-fermentationmentioning
confidence: 99%
“…The underlying mechanisms for electron transfer between electrodes and microbes were majorly investigated in a model dissimilatory metal reducing bacterium (DMRB) Shewanella oneidensis MR-1 ( Kracke et al, 2015 ; Kumar et al, 2017 ; Rowe et al, 2018 ). This strain was reported to use a broad spectrum of terminal electron acceptors, such as heavy metal minerals, fumarate, dimethyl sulfoxide, nitrate and thiosulfate ( Ikeda et al, 2021 ). S. oneidensis MR-1 employs several different strategies to capture electrons from the cathode, including cytochromes, nanowires and extracellular ESs ( Tremblay and Zhang, 2015 ).…”
Section: Introductionmentioning
confidence: 99%